COVID-19 à Goma : Perception, Adoption des mesures de protection et Santé mentale - Eric Kankunda, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Since the beginning of forced confinement, the residents of Goma, in particular, women have never ceased to be subjected, by the police, to numerous harassments going as far as gender-based violence because of the systematic adoption of barrier measures against COVID-19. Using the descriptive approach to the pandemic, 146 men and women participated in the survey. The results indicate that social media is the main source of